ASP210: a potent oligonucleotide-based inhibitor effective against TKI-resistant CML cells - Nemethova, Veronika; Babiakova, Petra; Teglasova, Boglarka; Uhelska, Lucia; Babelova, Andrea; Selc, Michal; Jakic, Kristina; Mitrovsky, Ondrej; Myslivcova, Denisa; Zackova, Marketa; Poturnayova, Alexandra; Batorova, Angelika; et al. (American journal of physiology. Cell physiology, 2024)
Clinical experience with tyrosine kinase inhibitors (TKIs) over the past two decades has shown that, despite the apparent therapeutic benefit, nearly 30% of patients with chronic myelogenous leukemia (CML) display primary resistance or intolerance to TKIs, and approximately 25% of those treated are forced to switch TKIs at least once during therapy due to acquired resistance. Safe and effective treatment modalities targeting leukemic clones that escape TKI therapy could hence be game changers in the professional management of these patients. Here, we aimed to investigate the efficacy of a novel therapeutic oligonucleotide of unconventional design, called ASP210, to reduce BCR-ABL1 mRNA levels in TKI-resistant CML cells, with the assumption of inducing their apoptosis. Imatinib- and dasatinib-resistant sublines of BCR-ABL1-positive MOLM-7 and CML-T1 cells were established and exposed to 0.25 and 2.5 μM ASP210 for 10 days. RT-qPCR showed a remarkable reduction of the target mRNA level by >99% after a single application. Cell viability was monitored daily by trypan blue staining. In response to the lack of driver oncoprotein BCR-ABL1, TKI-resistant CML cells underwent apoptosis regardless of the presence of the clinically relevant T315I mutation by day 5 after redosing with ASP210. The effect was selective for cancer cells, indicating a favorable safety profile for this therapeutic modality. Furthermore, the spontaneous uptake and high intracellular concentrations of ASP210 suggest its potential to be effective at relatively low doses. The present findings suggest that ASP210 is a promising therapeutic avenue for patients with CML who fail to respond to TKI therapy.NEW & NOTEWORTHY Effective treatment modalities targeting leukemic clones that escape tyrosine kinase inhibitor (TKI) therapy could be game changers in the professional management of patients displaying primary resistance, intolerance, or acquired resistance to TKIs. Although delivering authentic innovations today is more complex than ever, we developed a highly potent and safe oligonucleotide-based modality against BCR-ABL1 mRNA named ASP210 that effectively induces cell death in BCR-ABL1-positive TKI-resistant cells while sparing BCR-ABL1-negative healthy cells.
Keywords: bcr-abl fúzní proteiny; messenger RNA; nádorové buněčné linie; apoptóza; Protein Kinase Inhibitors; lidé; Fusion Proteins, bcr-abl; Imatinib Mesylate; Cell Line, Tumor; Antineoplastic Agents; Oligonucleotides; chemorezistence; protinádorové látky; RNA, Messenger; Humans; chronická myeloidní leukemie; imatinib mesylát; Dasatinib; viabilita buněk; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Cell Survival; inhibitory proteinkinas; dasatinib; oligonukleotidy; Drug Resistance, Neoplasm; Apoptosis